Plan de negocios para la fábrica de aguardiente artesanal Garcianos, del sitio Mendoza, cantón Junín - Macías Vera, María Antonieta (2020)
The objective of this study is to design an applicable business plan for the Garcianos artisanal brandy factory, in the Mendoza site, Junín canton, to allow them to improve their level of sales. For this, it was necessary to carry out a market study to identify its coverage and develop strategic planning that would allow the objectives to be achieved. Likewise, a technical study was applied to validate the viability of the operation of the business and then determine the profitability of the proposal, through the study of income and expenses. The methodology used was descriptive, deductive and inductive, bibliographic research was used to support the study variables, field research to auscultate data and information through the application of survey instruments to a sample of 373 people from the consumer market and interview with the owner of the Garcianos artisan brandy factory. This research was carried out in four phases: Market study to identify its coverage, technical study that validates the viability of the business operation, determination of the profitability of the proposal, through the study of income and expenses; and, the strategic planning scheme that contributes to the improvement of the current situation. The results obtained allowed concluding the viability of the operation and profitability of the business, considering that it has great opportunity within the segment towards which it is directed, as it is a pioneer in the legal production of artisan liquor.